Cytological characteristics prior to the diagnosis of cervical cancer in women from Medellin (Colombia) - Osorio-Castaño, Jhon H.; Pérez-Villa, Marjorie; Montoya-Zapata, Claudia P.; Cardona-Restrepo, Fernando A. (Universidad y Salud, 2020)
Introduction: Currently, cervical cancer continues to be an important disease because of its high incidence and mortality. Even though its etiology (Human Papilloma Virus infection) and screening methods (conventional cytology and HPV-DNA test) are well known, understanding the various characteristics associated with the appearance of cervical cancer is fundamental. Objective: To describe the cytological characteristics that precede the diagnosis of cervical cancer in women diagnosed in a health care institution from the city of Medellín. Materials and methods: A descriptive study. The clinical records corresponding to women with a confirmed diagnosis of cervical cancer between 2012 and 2017 were used. Also, the citology results obtained before the diagnosis were reviewed. An univariate analysis was carried out in oder to describe the study variables. Results: The sample size of women with cervical cancer was 714, the age median was 51 years old (interquartile range: 42-60), the most frequent cytological alteration was high-grade intraepithelial lesion (33.8%), and the main diagnosed cancer type was squamous cell carcinoma (70.6%). Conclusions: Results showing an altered cytology are indicators of cervical cancer risk. Therefore, it is important to continue with the stablished screening protocol.